Laser‐Annealing of Thermoelectric CuFe0.98Sn0.02O2 Films Produced by Powder Aerosol Deposition Method. Issue 22 (5th October 2020) - Nazarenus, Tobias; Kita, Jaroslaw; Moos, Ralf; Exner, Jörg
Abstract: Powder aerosol deposition (PAD) is a unique coating method that allows the fabrication of dense ceramic films on a variety of substrates at room temperature. This spraying process can produce film thicknesses of several micrometers within minutes without the use of binders or other liquids. Although the functional properties of the well‐adhering films are already present in the as‐deposited state, the functional film properties are often reduced by several orders of magnitude. To recover bulk‐like values, the samples are typically thermally post‐deposition‐treated in a furnace. In contrast, in this work, the films are locally annealed by a frequency‐tripled Nd:YAG laser (λ = 355 nm). A thermoelectric material, doped copper delafossite, is sprayed via PAD and the influence of frequency‐tripled Nd:YAG laser irradiation on the electronic and morphological film properties is investigated in detail. A very thin, glass‐like surface layer forms whose electronic conductivity is three orders of magnitude higher than in the as‐deposited state. This is proven by electrical impedance spectroscopy, microscopic images, and FEA‐simulations. Abstract : Powder aerosol deposition (PAD) is a unique ceramic coating method in which bulk‐like coating properties can be achieved by a thermal post treatment. In this article, a simulation supported experimental study on the influence of laser irradiation (λ = 355 nm) on electronic and optic properties of thermoelectric CuFe0.98 Sn0.02 O2 ‐PAD films is presented.